Impact of continuous self-assessment on the learning of medical students - Kaur, Manjinder; Singh, Harpreet; Badyal, Dinesh (International Journal of Research in Medical Sciences, 2017)
Background: During the learning process, feedback plays an important role by helping the learner in recognition of the desired goal, evidence about present position, and some understanding of a way to close the gap between the two Objective of the study was to improve learning by using continuous self-assessment as a tool among the medical students, this would inculcate the habit of self-directed and regular learning habits. Methods: The study was conducted on 79 first year undergraduate medical students, where they were taught a topic from physiology and they were exposed to the weekly self-assessment sessions. The tests were corrected by the students themselves and thereafter discussed in the class by the teacher. These response sheets were collected and scrutinized by the teacher and feedback were given to each student. The progress record was maintained by the teacher showing the response of the students in terms of attendance and performance. The average scores of these students (study group) were compared with the scores of the previous batch (control group. The focused group discussion was also carried out among the study group and responses were recorded. Results: A significant (p<0.05) improvement was observed in the score of the students during the continuous self-assessment sessions along with an increase of 46% marks in the students undergoing this program as compared to the senior batch who were not exposed to continuous self-assessment tool. The focused group discussions on the perception of the self-assessment session yielded a satisfactory response among the study group, which documented the stress levels and better performance during semester. Conclusions: This study provided an early feedback to the learners resulting in continuous improvement by identifying their strengths, weaknesses, the learning gaps and making them self-directed learners.